The use of a surgical logbook to improve training and patient safety: A retrospective analysis of 6 years' experience in Bristol, UK - Elizabeth Wasson; Charankumal Thandi; Adam Bray (Wiley, 2024)
Abstract Background Logbooks can be a useful educational tool. Although their use in medical training has been greatly explored, there is limited research into their application throughout a clinician's career. We created a surgical logbook to allow clinicians to record their skin surgery procedures and reflect on the histological diagnosis and clearance margins achieved. Objectives We provide a retrospective analysis to evaluate the usefulness of the logbook as an analytical and educational tool in a dermatology department, particularly for maintaining exemplary complete excision rates. Methods Data was collected from clinicians who conducted skin surgery in Bristol, UK. Cases were entered at the time of surgery, collecting data on body site, clinical margin, suspected diagnosis, type of procedure and closure. Following receipt of histological results, data on histological excision margins and tumour type was entered. Each clinician submitted data for a minimum of 3 months each year, and data collection ran from April 2012 until March 2018. Results Data from 5161 excision surgeries was collected over the 6‐year period. On histological diagnosis, excisions constituted 50% Basal Cell Carcinoma (BCC), 12% Squamous Cell Carcinoma (SCC), 9% Malignant Melanoma (MM) and 1% Lentigo Maligna (LM), and 28% 'Other' (rarer malignancies, melanoma wide local excision scars and pre‐cancerous/benign lesions). The department was found to have good diagnostic concordance: BCC 92%, SCC 87%, MM 80% and LM 53%. Overall complete excision rate was high at 97.07%. The most successfully excised cancer was BCC (97.50%), then SCC (97.14%) MM (96.48%) and LM (95.23%). The department provided many complex surgeries including 8.3% flaps and 8.5% grafts. Average lesion diameter was 11 mm (range 2-90 mm). There was a significant improvement in excision rates seen over the years for BCC, MM and LM. Although there was no significant difference found for SCC, this group began the study with already high clearance rates. Conclusion This surgical logbook supports improved training and continues professional development. We encourage more departments to use this logbook and share the data that they produce. This could improve their excision rates, patient experience, and save them up to £28 000 per year.